HIKAYAT NABI BERCUKUR : Seni Dalam Budaya Nusantara - Nurfitria Dewi; Wangiman Wangiman; Adi Warma; Zainur Huda; Desri Novita (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
Hikayat is a type of old prose that tells about the life history of a character. The saga contains stories of the goodness and glory of the character during his lifetime. Saga of the Prophet Shaving (Hikayat Nabi Bercukur) in the Malay Archipelago society is a source of knowledge related to art and culture in the Archipelago, which also contains religious values. The purpose of this study is to explain the description Saga of the Prophet Shaving (Hikayat Nabi Bercukur) and the function of the script. The method used in this study is descriptive qualitative. The results of the study show that the manuscript Saga of the Prophet Shaving (Hikayat Nabi Bercukur) is quite popular, as evidenced by the many copies of the text in various languages. Manuscripts are also stored in the PNRI and foreign museums, namely Leiden and London. Some of the functions of the script are: first, fostering a spirit of heroism; second, the didactic function that teaches education about monotheism; third, entertaining; fourth, perpetuating all kinds of events that have been experienced by the caliph, namely the Prophet Muhammad.